Metals and limnological variables in an urban reservoir: compartmentalization and identification of potential impacted areas - Cardoso-Silva, Sheila [UNESP]; López-Doval, Julio Cesar; Moschini-Carlos, Viviane [UNESP]; Pompêo, Marcelo (Springer Nature, 2018)
Reservoirs in urban areas are used for different purposes and are liable to different types of pressures that can cause the loss of chemical and biological quality, hence diminishing their ecological, economic, and cultural benefits. Here, a study of surface water heterogeneity was undertaken at the Guarapiranga urban reservoir (São Paulo, Brazil) in order to improve understanding of the structure and functioning of these ecosystems. Sampling was performed during the dry and rainy seasons at 33 sites. Limnological variables and total contents of the metals cadmium, nickel, lead, and zinc were analyzed. The risks associated with the metals were evaluated based on the toxicity unit approach. A principal component analysis enabled differentiation of the reservoir into six different areas. Some of the most powerful discriminatory variables (nutrients and metals) showed the existence of anthropogenic impacts on the system. The most strongly affected compartments were located in the following: (1) upstream area, under the influence of the Parelheiros stream, with the highest total phosphorus levels (318 mg L−1) and (2) dam area, with high values for total nitrogen, suspended organic matter, total solids, and pH. The results for the dam compartment were a consequence of substantial urbanization and a longer residence time. Despite high levels of cadmium during the rainy season, no significant potential risk for zooplankton was observed. The data indicated the need to control unauthorized land occupation and to implement adequate sanitation in the Guarapiranga watershed. This research provides information that should assist water resource agencies in the sustainable management of urban reservoirs.
Keywords: Cadmium contamination; Spatial heterogeneity; Urban impact; Water quality